New insights into the symbiosis between Zanclea (Cnidaria, Hydrozoa) and scleractinians. (27th August 2014) - Montano, Simone; Arrigoni, Roberto; Pica, Daniela; Maggioni, Davide; Puce, Stefania
<x xml:space="preserve">Abstract</x> Hydroids in the genus Zanclea are a recently discovered component of the fauna associated with reef‐building corals. The phylogenetic relationships among these species are not well known. The present work is based on field surveys in the Republic of Maldives, and for the first time, morphological and molecular analyses are integrated to distinguish a new hydroid species and provide new information on the ecology of this symbiosis. This new hydroid, Zanclea gallii sp. n., was associated with the scleractinian Acropora muricata; it was living sympatrically with its congener Zanclea sango, which was observed for the first time at this locality on the new scleractinian host Pavona varians. The relationships between these two hydroids and other available scleractinian‐associated Zanclea were investigated using two molecular markers, nuclear 28S rDNA and mitochondrial 16S rRNA. Zanclea gallii sp. n. and Z. sango were recovered as distinct lineages within a monophyletic group of scleractinian‐associated Zanclea based on both molecular and morphological data. All Zanclea species that were observed living in association with scleractinians belong to the 'polymorpha group' and share the morphological characteristic 'polymorphic colony'. The genus Leptoseris is the 16th host coral identified for Zanclea. Compared with the frequency of the Z. gallii sp. n. association with A. muricata and Z. sango with the scleractinian P. varians, the latter is twice as common; however, the former exhibited higher Zanclea polyps concentrations over the colony surface. Overall, the Zanclea survey indicates that these diminutive hydroids are more commonly associated with coral than previously known.